SEBARAN PASAK BUMI (Eurycoma longifolia Jack.) DI BERBAGAI KETINGGIAN TEMPAT PADA KAWASAN HUTAN LINDUNG GUNUNG AMBAWANG BUKIT BENDERA KECAMATAN TELUK PAKEDAI Distribution Pasak Bumi (Eurycoma Longifolia Jack.) Height In Various Places In Protected Forest - Erwanto, Wahyu; Muin, Abdurrani; Dewantara, Iswan (Universitas Tanjungpura, 2014)
The purpose of this study was to determine the distribution of the pasak bumi (Eurycoma longifolia Jack.), the number of population and associations pasak bumi (Eurycoma longifolia Jack.) based on the level of 0-100 m altitude, 100 to 200 m, 200-300 m and 300 m in above sea level to the top. Vegetation analysis conducted by purposive sampling method with a single plot size of 40 mx 40 m. Distribution pasak bumi (Eurycoma longifolia Jack.) tends to experience the difference in altitude from sea level with a growing number of individuals at each altitude increment. Pasak bumi (Eurycoma longifolia Jack.) is usually found at an altitude of 300-325 m at sea level differences as much as 511 people with an index value of 128.60% critical. At an altitude of 300 m above the earth peg type is a type that is very dominant to other vegetation types. Pasak bumi (Eurycoma longifolia Jack.) At an altitude of 0-100 m above sea level associated with pasir-pasir (Stemonurus secundiflorus Blume) and gedebok, altitude 100-200 m above sea level with cempedak air (Artocarpus teysmanni), height of 200 -300 m above sea level with ilas (Parastemon urophyllum) and resak (Vatica dulitensis Sym.) and at an altitude of 300 m above sea level with ilas (Parastemon urophyllum). Keywords: Pasak Bumi (Eurycoma longifolia Jack.), the distribution based on the altitude, the association.